Identifying and Prioritizing the Performance Criteria of Denim Washing Industry in Bangladesh Using Analytic Hierarchy Process - Karim, Md. Rezaul; Islam, Md. Monirul; Ali, Mohammad (European Scientific Journal, ESJ, 2020)
In the midst of the negative growth of textile and RMG industries, the mother industry of Bangladesh, the denim industry, has been doing its part incessantly. While the prospect of the denim industry looks promising from the last few years, the factors that drive this industry forward remain unanswered. Among the process chain of denim manufacturing, most value addition occurs in denim washing. This paper focuses on identifying and prioritizing the performance criteria of the denim washing sector in particular. In this context, export-oriented denim washing factories are chosen and the identified criteria are evaluated by using Analytical Hierarchy Process (AHP). This study is qualitative in nature and the secondary data about the factors were collected initially through review of previous literature, magazines, books, and newspapers. A structured questionnaire was developed to collect data from 35 factories. The results of the study show that cost, time, quality, and flexibility are the critical factors for success. The findings also seem to be consistent in general in regard to the test results, and it provides insight for improvement in the denim washing industry of Bangladesh.